1976
DOI: 10.1136/bmj.2.6035.559
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in dental surgical practice.

Abstract: Sixty-one dental surgeons at King's College Hospital were interviewed to establish the incidence of attacks of viral hepatitis and to relate this to environmental risk factors. Six (10",,) had a history of hepatitis, in one case due to infection with the hepatitis B virus. Screening blood for HBsAg by radioimmunoassay showed no carriers of the antigen, but transient antigenaemia was observed in one dentist. Antibody to HBsAg, tested by radioimmunoassay, was detected in four dentists (7)0), only one of whom had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, these dentists also believed they had always taken appropriate precautions [47]. In 1976, a study showed that approximately 50% of dental surgeons had knowingly treated HBV-infected patients, and some dentists had treated patients with HBV infection many times.…”
Section: Knowledge Of Dentistsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these dentists also believed they had always taken appropriate precautions [47]. In 1976, a study showed that approximately 50% of dental surgeons had knowingly treated HBV-infected patients, and some dentists had treated patients with HBV infection many times.…”
Section: Knowledge Of Dentistsmentioning
confidence: 99%
“…PatientsÕ attendance in dental clinics exposes them to two risks: first, the probability of cross-infection from one patient to another from an infected dental instrument; and second, the potential hazard of an infected dentist [47]. Because of HBV vaccination, the infection rate has decreased significantly.…”
Section: Knowledge Of Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hepatitis-B (surface) antigen (HBsAg) is present in] saliva (Heathcote, Gateau and Sherlock, 1974;Villarejos et al, 1974), other body secretions, and in the blood of chronic carriers of the hepatitis-B virus (HBV). Dentists come into close contact with saliva and blood in the course of their work, and they have been shown to be particularly at risk from infection by this virus (Feldman and Schiff, 1975;Moseley and White, 1975;Goubran et al, 1976). One might expect that anaesthetists would share the increased risk.…”
mentioning
confidence: 99%